Screening of some cassava starches for their potential applications in custard and salad cream productions - Akinwale, T.E.; Niniola, D.M; Abass, A.; Shittu, T.A.; Adebowale, A.; Awoyale, W.; Awonorin, S.; Adewuyi, S.; Eromosele, C.O. (Springer, 2017)
Custard powder and salad cream are two food products commercially manufactured using different quantities of corn starch. This study aimed at determining the physicochemical properties of some starches extracted from some white and yellow root cassava varieties. The prospective applicability of the cassava starches in custard powder and salad cream production was also determined. The physical, chemical and functional properties of eight cassava starches were determined using standard analytical procedures. Sensory acceptability of the products was also determined using untrained consumer group. Products made from corn starch were used as the reference samples. The physical, chemical and functional properties of the cassava starches varied significantly (p < 0.05). The results of multivariate data analysis (principal component and cluster analyses) showed that it was difficult to completely discriminate starches from the yellow fleshed and white fleshed cassava roots. Texture was the most important sensory attribute determining the two products’ acceptability. Starch powder dispersibility was found to have significant influence (p < 0.05) on the sensory acceptability of the two products. However, starch from a yellow fleshed root (TMS 01/1368) was the most preferred for salad cream making while starch from a white fleshed root (TMS 30572) was the most preferred for making custard powder. The starches showed high potential to replace corn starch for the respective product manufacture.